Organizational Behavior: The Harmony Between People, Systems, and Leadership - Carolina, Sisi Yulisia; Silalahi , Ricky Daud Nelson; Rahayu , Angelia Tri; Bimantoro , Satrio (Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
Organizational behavior is a crucial field in modern management that examines how individuals, systems, and leadership dynamically interact to achieve collective goals. This article integrates findings from various international sources discussing the three key elements of organizational behavior: human motivation and attitudes, organizational systems of structure and control, and leadership as the bridge between both. The findings indicate that organizational effectiveness depends on maintaining harmony between structural control and humanistic approaches emphasizing motivation, communication, trust, and participative leadership. In the digital era, balancing system efficiency and human well-being becomes essential for sustainable organizational growth.